KONSEP POLA ASUH ANAK PERSPEKTIF IMAM AL-GHAZALI “STUDI ATAS KITAB IHYA' 'ULUMUDDIN’’ - Ahmad Hujaji; Jasminto Jasminto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Morals are traits that are inherent in the soul and trigger spontaneous actions, where ImamlAl-Ghazalijinjthejbook Ihya' 'Ulumiddin emphasizes thejimportancejof accustoming children to good morals from an early age, remembering that a child's heart is like a blank piece of paper that can easily absorb everything, so this habituation is a must for parents as full responsibility for God's mandate to care for, raise and educate children with love. This research, which uses a documentation approach with primary data from Al-Ghazali's writings and secondary data from relevant sources, Focusesjonjtwojmainjquestions: what is the concept of good and bad parenting patternsjaccordingjtojImamjAl-GhazalijinjIhya' 'Ulumiddin.The research results show that good parenting according to Al-Ghazali includes cultivating manners, developing noble character, prioritizing religious education, monitoring the social environment, providing role models, teaching balance injthejworldjandjthejherejafter,jasjwelljas education with love and wisdom. On the other hand, bad parenting is characterized by tolerating bad habits, neglect, allowing children to mix with negative environments, excessive criticism, not teaching manners, worldly indulgence, not providing religious education, allowing children to take other people's rights, and not maintaining good manners in speaking.